PENGARUH MODEL PROBLEM BASED LEARNING TERINTEGRASI LITERASI SAINS UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK TINGKAT SMA - Wulandari, Devita; Dwikoranto; Setiani, Rahyu (IPF: Inovasi Pendidikan Fisika, 2025)
This research aims to determine the effect of the Problem Based Learning model which is integrated with scientific literacy to improve critical thinking skills. This type of quasi-experimental research used random sampling techniques. The research subjects were class X students at Wahid Hasyim Karanggeneng High School using two classes, namely class X.E3 as the experimental class and X.E4 as the control class. The research instrument consists of an implementation sheet, test sheet and response questionnaire. The research results show that the Problem Based Learning model which is integrated with scientific literacy is implemented very well with an average percentage of 98.8%. The increase in critical thinking skills as measured by N-Gain obtained an average of 0.71, which means that the experimental class was in the high category, and a positive response was obtained from students with an average percentage of 92.2%, this shows that there is an influence Problem Based Learning model integrated with scientific literacy to improve critical thinking skills.